Грбовите на Македонија во западноевропски извори - The Coat of Arms of Macedonia in Western European Sources - Nacevski, Ivan (Македонски хералд - Macedonian Herald, 2023)
Sources of the coats of arms of Macedonia can be distinguished from several aspects such as their date, language, symbols, etc. However, what seems to be key is where they appear. Thus, based on the place of appearance of the sources with the Macedonian coat of arms, we can distinguish two groups. The first group is represented by the sources from Illyrian heraldry. The second group consists of sources that are not part of Illyrian heraldry which can be termed the non-Illyrian group. Due to its breadth and diversity, the non–Illyrian group can itself be divided into two subgroups. The first subgroup consists of the coats of arms of the king of Macedonia or just Macedonia, and the second consists of the attributed coats of arms of Alexander the Great. In addition, a third subgroup can be distinguished, which includes the coats of arms of Emathya as well as the coats of arms of certain Macedonian rulers, cities, etc. As the coat of arms of Alexander the Great is itself a large topic it will not be the subject of this paper. Instead, the focus of this paper will be the coats of arms of the first subgroup of non–Illyrian heraldry. In addition, sources from the third subgroup will be presented.